Heavy metals in the air and their adverse effects on human being health; IFOST 2012; Vol. 1 - Osipova N. A. Nina Aleksandrovna; Yankovich E. P. Elena Petrovna; Yazikov Y. G. Yegor (Egor) Grigoryevich; Talovskaya A. V. Anna Valerievna (Section 1. Chemical engineering and "Green technology", 2012)
Spatial distribution analysis of environmental health risk in the Tomsk area was performed. Risk estimation was done according to standard methodology on the basis of geochemical data from thesnow cover of the area. The city territory was divided into areas with different levels of ecological damage and human health risk values. The city territory was ranked in accordance to risk level from exposure of trace elements contained in atmospheric dust.